Pregnancy outcomes of women with coexisting systemic lupus erythematosus flare and preeclampsia. Issue 3 (May 2015) - Aoki, Shigeru; Mochimaru, Aya; Yamamoto, Yuriko; Kurasawa, Kentaro; Takahashi, Tsuneo; Hirahara, Fumiki
Abstract Objectives. Systemic lupus erythematosus (SLE) flare and preeclampsia are difficult to differentiate from each other and occasionally coexist; This study aimed to analyze cases requiring termination of pregnancy due to SLE flare or preeclampsia and to elucidate the association between these two conditions; Methods. Out of 71 pregnancies in 60 women managed for SLE-complicated pregnancies who delivered at or after 22 weeks' gestation at a tertiary center, 7 pregnancies were terminated due to uncontrollable severe SLE flare or severe preeclampsia We retrospectively analyzed the clinical courses and laboratory findings of these 7 cases to determine whether their pathological conditions were attributable to SLE flare alone, preeclampsia alone, or the coexistence of these two conditions. Results. One of the 7 cases had preeclampsia alone, two had SLE alone, and four had both conditions. The coexistence of preeclampsia and SLE was thus the most common condition. In cases with both conditions, SLE flare had preceded preeclampsia, thereby making treatment after delivery difficult. Conclusion. Severe SLE flare often preceded severe preeclampsia and worsened after delivery. When differentiating severe SLE flare from severe preeclampsia is difficult during pregnancy, women should be regarded as having SLE flare rather than preeclampsia and aggressively treated.